MENINGKATKAN ADAPTASI AIR MELALUI PERMAINAN AMPAR-AMPAR BOLA PADA TK BINA CITRA CENDEKIA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The aim of the research is to improve the adaptation of children in the water via Ampar-Ampar ball game, eliminating the fear of children in the pool, increase the interest and motivation of the child to the pool, assist teachers in teaching swimming through a game Ampar-Ampar ball, increasing the teacher's creativity in learning. The method used is a method penelitiaan class act. Stages of research are planning that planning has been done in this research is to create a work program, making research instruments, tools and materials preparation. The results showed that the cycle I obtained 25% of the children dared to adapt in the water. Cycle II result 50% of the children dared to adapt in the water, and the cycle continued III using a ball game ampar-ampar acquired 90% of the children dared to adapt in the pool. It can be concluded that the level of kindergarten children Bina Citra adaptation Scholar Ungaran Semarang in the pool can be increased by using the method of playing Ampar-Ampar ball..